SNR‐efficient distortion‐free diffusion relaxometry imaging using accelerated echo‐train shifted echo‐planar time‐resolving imaging (ACE‐EPTI). Issue 1 (28th February 2022) - Dong, Zijing; Wang, Fuyixue; Wald, Lawrence; Setsompop, Kawin
Abstract : Purpose: To develop an efficient acquisition technique for distortion‐free diffusion MRI and diffusion‐relaxometry. Methods: A new accelerated echo‐train shifted echo‐planar time‐resolved imaging (ACE‐EPTI) technique is developed to achieve high‐SNR, distortion‐free diffusion, and diffusion‐relaxometry imaging. ACE‐EPTI uses a newly designed variable density spatiotemporal encoding with self‐navigators for phase correction, that allows for submillimeter in‐plane resolution using only 3‐shot. Moreover, an echo‐train‐shifted acquisition is developed to achieve minimal TE, together with an SNR‐optimal readout length, leading to ∼30% improvement in SNR efficiency over single‐shot EPI. To recover the highly accelerated data with high image quality, a tailored subspace image reconstruction framework is developed, that corrects for odd/even‐echo phase difference, shot‐to‐shot phase variation, and the B0 field changes because of field drift and eddy currents across different dynamics. After the phase‐corrected subspace reconstruction, artifacts‐free high‐SNR diffusion images at multiple TEs are obtained with varying T2 * weighting. Results: Simulation, phantom, and in vivo experiments were performed, which validated the 3‐shot spatiotemporal encoding provides accurate reconstruction at submillimeter resolution. The use of echo‐train shifting and optimized readout length improves the SNR‐efficiency by 27%‐36% over single‐shot EPI. The level of image distortion was also evaluated, which shows no noticeable susceptibility and eddy‐current distortions in ACE‐EPTI images that are common in EPI. The time‐resolved acquisition of ACE‐EPTI also provides multi‐TE images for diffusion‐relaxometry analysis. Conclusion: ACE‐EPTI was demonstrated to be an efficient and powerful technique for high‐resolution diffusion imaging and diffusion‐relaxometry, which provides high SNR, distortion‐ and blurring‐free, and time‐resolved multi‐echo images by a fast 3‐shot acquisition.